Antifibrinolytics (lysine analogues) for the prevention of bleeding in patients with haematological malignancies (Review). - Wardrop, D; Estcourt, L; Doree, C; Stanworth, S; Murphy, M; Brunskill, S; Trivella, M (Wiley, 2013)
Background Patients with haematological disorders are frequently at risk of severe or life-threatening bleeding as a result of thrombocytopenia. This is despite the routine use of prophylactic platelet transfusions (PlTx) to prevent bleeding once the platelet count falls below a certain threshold. PlTx are not without risk and adverse events may be life-threatening. A possible adjunct to prophylactic PlTxs is the use of antifibrinolytics, specifically the lysine analogues tranexamic acid (TXA) and epsilon aminocaproic acid (EACA). Objectives To determine the efficacy and safety of antifibrinolytics (lysine analogues) in preventing bleeding in patients with haematological disorders. Search methods We searched for randomised controlled trials (RCTs) in the Cochrane Central Register of Controlled Trials (CENTRAL Issue 12, 2012), MEDLINE (1948 to 10 January 2013), EMBASE (1980 to 10 January 2013), CINAHL (1982 to 10 January 2013), PubMed (e-publications only) and the Transfusion Evidence Library (1980 to January 2013). We also searched several international and ongoing trial databases to 10 January 2013 and citation-tracked relevant reference lists. Selection criteria RCTs involving patients with haematological disorders, who would routinely require prophylactic platelet transfusions to prevent bleeding. We only included trials involving the use of the lysine analogues TXA and EACA. Data collection and analysis Two authors independently screened all electronically derived citations and abstracts of papers, identified by the review search strategy, for relevancy. Two authors independently assessed the full text of all potentially relevant trials for eligibility, completed the data extraction and assessed the studies for risk of bias using The Cochrane Collaboration's 'Risk of bias' tool. We requested missing data from one author but the data were no longer available. The outcomes are reported narratively: we performed no meta-analyses because of the heterogeneity of the available data. Main results Of 470 articles initially identified, 436 were excluded on the basis of the title and abstract. We reviewed 34 full-text articles from which four studies reported in five articles were eligible for inclusion. We did not identify any RCTs which compared TXA with EACA. We did not identify any ongoing RCTs. One cross-over TXA study (eight patients) was excluded from the outcome analysis because data from this study were at a high risk of bias. Data from the other three studies were all at unclear risk of bias due to lack of reporting of study methodology. Three studies (two TXA (12 to 56 patients), one EACA (18 patients)) reported in four articles (published 1983 to 1995) were included in the narrative review. All three studies compared the drug with placebo. All studies reported bleeding, but it was reported in different ways. All three studies suggested antifibrinolytics reduced the risk of bleeding. The first study showed a difference in average bleeding score of 42 in placebo (P) versus three (TXA). The second study only showed a difference in bleeding episodes during consolidation chemotherapy, with a mean of 2.6 episodes/patient (standard deviation (SD) 2.2) (P) versus a mean of 1.1 episodes/patient (SD 1.4) (TXA). The third study reported bleeding on 50% of days at risk (P) versus bleeding on 31% of days at risk (EACA). Two studies (68 patients) reported thromboembolism and no events occurred. All three studies reported a reduction in PlTx usage. The first study reported a difference of 222 platelet units (P) versus 69 platelet units (TXA). The second study only showed a difference in total platelet usage during consolidation chemotherapy, with a mean of 9.3 units (SD 3.3) (P) versus 3.7 (SD 4.1) (TXA). The third study reported one PlTx every 10.5 days at risk (P) versus one PlTx every 13.3 days at risk (EACA). Two studies reported red cell transfusion requirements and one study found a reduction in red cell transfusion usage. One study reported death due to bleeding as an outcome measure and none occurred. Only one study reported adverse events of TXA as an outcome measure and none occurred. None of the studies reported on the following pre-specified outcomes: overall mortality, adverse events of transfusion, disseminated intravascular coagulation (DIC) or quality of life (QoL). Authors' conclusions Our results indicate that the evidence available for the use of antifibrinolytics in haematology patients is very limited. The only available data suggest that TXA and EACA may be useful adjuncts to platelet transfusions so that platelet use, and the complications associated with their use, can be reduced. However, the trials were too small to assess whether antifibrinolytics increased the risk of thromboembolic events. Large, high-quality RCTs are required before antifibrinolytics can be demonstrated to be efficacious and safe in widespread clinical practice.